The Effect of Injury-Related Characteristics on Changes in Marital Status after Spinal Cord Injury - Effat MERGHATI KHOI; Sahar LATIFI; Fereshteh RAHDARI; Hania SHAKERI; Farid ARMAN; Davood KOUSHKI; Abbas NOROUZI JAVIDAN; Seyede-Mohadeseh TAHERI OTAGHSARA (Tehran University of Medical Sciences, 2015)
Background: Spinal cord injury (SCI) imposes a significant burden on the social and marital life. Here, we assessed the divorce rate and changes in marital status among a sample of Iranian individuals with SCI. Methods: Referred patients to Brain and Spinal Cord Injury Research Center were invited to participate in this cross-sectional investigation. The Main exclusion criteria were coincidental brain injury, history of chronic diseases before SCI and substance use. Demographic characteristics (including age, gender, educational level, marital status before and after injury and duration of marriage) and Injury characteristics (level of the injury, American spinal injury association (ASIA) scale and Spinal cord independence measure III (SCIM)) were collected. Results: Total of 241 subjects with SCI participated in this investigation (164 (68%) male and 77 (32%) female). Among men, 16.5% [95% CI: 10.81%-22.18%] and among women 18.2% [95% CI: 9.58%-26.81%] got divorced after injury. Duration of marriage before injury was significantly related to lower divorce rate (P< 0.001 and 0.016 in men and women, respectively). Injury characteristics had no relationship with marital longevity. Age was a protective factor against marital dissolution only in men (P< 0.004). Conclusion: Our study revealed the divorce rate of 17% [95% CI: 13%-20.9%] after SCI in a sample of Iranian population. The protective influence of age in maintenance of marriage was only detected in men, which proposes existence of a sexual polymorphism in the role of age. Divorce rate was similar between two genders and injury characteristics were not related to divorce rate as well.   Keywords: Marital status, Spinal cord injury, Divorce, Iran